2010
DOI: 10.1038/nm.2207
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic AMPK and fatty acid metabolism mediate thyroid regulation of energy balance

Abstract: Thyroid hormones have widespread cellular effects; however it is unclear whether their effects on the central nervous system (CNS) contribute to global energy balance. Here, we demonstrate that either whole body hyperthyroidism or central administration of triiodothyronine (T3) decreases the activity of hypothalamic AMP-activated protein kinase (AMPK), increases sympathetic nervous system (SNS) activity and upregulates thermogenic markers in brown adipose tissue (BAT). Inhibition of the lipogenic pathway in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
719
6
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 598 publications
(784 citation statements)
references
References 60 publications
45
719
6
4
Order By: Relevance
“…It is not clear whether non-genomic effect of TR also plays a role in sustaining energy metabolism. A recent study showed that AMPK activity is regulated by thyroid hormone in CNS (López et al, 2010); however, the authors did not point out whether such regulation belongs to non-genomic action of TR or not. In addition to AMPK signaling, MAPK and PI3K/AKT signaling have been shown to be regulated by thyroid hormone.…”
Section: Non-genomic Effect Of Trmentioning
confidence: 92%
“…It is not clear whether non-genomic effect of TR also plays a role in sustaining energy metabolism. A recent study showed that AMPK activity is regulated by thyroid hormone in CNS (López et al, 2010); however, the authors did not point out whether such regulation belongs to non-genomic action of TR or not. In addition to AMPK signaling, MAPK and PI3K/AKT signaling have been shown to be regulated by thyroid hormone.…”
Section: Non-genomic Effect Of Trmentioning
confidence: 92%
“…For example, thyroid hormone directly induces the expression of thermogenic genes in brown adipocytes through the actions of thyroid receptors and also functions centrally to activate BAT [142][143][144] . Along similar lines, the neurotransmitter orexin augments BAT function by regulating sympathetic outflow and through directly promoting brown fat precursor differentiation 145,146 (Fig.…”
Section: Sympathetic Nerve Control Of Brown and Beige Fatmentioning
confidence: 99%
“…Both leptin and the thyroid hormone T3 were reported to inhibit or down-regulate AMPK in the hypothalamus, and this was associated with increased activity of the sympathetic nervous system. This caused increased fat oxidation in skeletal muscle in response to leptin, a response that had a longer time course than the direct effects of the hormone on muscle , and increased expression of markers of thermogenesis in brown adipose tissue in response to T3 (Lopez et al 2010). These effects help to explain how these hormones increase energy expenditure and/or heat production.…”
Section: Regulation Of Ampk By Metabolic Stresses Cytokines Drugsmentioning
confidence: 99%